Structural design of low-rise buildings in cold-formed steel, reinforced masonry, and structural timber - Mujagic, J. R. Ubejd (New York : McGraw-Hill, 2012)
'A concise, practical guide to structural design using steel, masonry, and timber Structural Design of Low-Rise Building in Cold-Formed Steel Reinforced Masonry, and Structural Timber authoritatively covers the primary aspects of structural design of low-rise buildings in the most common materials--cold-formed steel, reinforced masonry, and structural timber. Cold-formed steel was recently added to the NCEES (National Council of Examiners for Engineering and Surveying) structural exams, and this book also serves as a complete Professional Engineer/Structural Engineer exam study guide.Structural Design of Low-Rise Building in Cold-Formed Steel Reinforced Masonry, and Structural Timber Discusses concepts associated with day-to-day design Covers Steel Joist Institute (SJI) open-web joist systems Includes the most recent changes in fundamental code requirements pertaining to structural timber, reinforced masonry, and cold-formed steel Addresses loading requirements for low-rise buildings Presents the most important code changes pertaining to IBC-based design of structural masonry, cold-formed steel, and structural timber/wood'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Structural analysis (Engineering).; Buildings